2017
DOI: 10.1016/j.jvs.2016.05.090
|View full text |Cite
|
Sign up to set email alerts
|

Late rupture of abdominal aortic aneurysm after endovascular repair

Abstract: This study confirmed that endovascular AAA repair does not prevent rupture in all patients. The data suggest that rupture, when it does occur, may not be accompanied by such major hemodynamic changes and higher mortality rate as with rupture of an untreated AAA. Strict surveillance and follow-up are required, especially in patients with relatively large initial AAA diameter or presence of endoleak and graft migration, to reduce the rate of ruptures after endovascular repair. Complete prevention will remain cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…After reviewing titles, abstracts and full-text versions of these articles, five studies fulfilled the inclusion criteria and were included in qualitative synthesis. 1418 Two studies originated from the same institution, and the data from the older study were included in the more recent report which was finally included in the quantitative synthesis which involved four studies. The literature flow chart is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing titles, abstracts and full-text versions of these articles, five studies fulfilled the inclusion criteria and were included in qualitative synthesis. 1418 Two studies originated from the same institution, and the data from the older study were included in the more recent report which was finally included in the quantitative synthesis which involved four studies. The literature flow chart is presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…11 In the latter 11 years of the study, the mean time to rupture from the index procedure and last follow-up was 4.9 years (range 1.7-13.2 years) and 118 days (range 2.9-297 days), respectively. 11 Alarmingly, Greiner et al 12 retrospective single-center analysis of ruptured AAAs from 2011 to 2013 reported that of the ruptured AAAs presenting to an institution, 20% (6 out of 30) were late ruptures after EVAR.…”
Section: Late Rupture: Epidemiologymentioning
confidence: 90%
“…7 A lower incidence of 0.9% (95% CI: 0.77-1.05) with a mean time to rupture of 37 months was reported in a recent metaanalysis of case series and cohort studies. 7 The studies performed by May et al 10 and subsequently by Rajendran et al 11 which compared the outcomes of late rupture after EVAR to rupture after no intervention found 3.1% (40 out of 1288) of patients during a 22-year period had a late rupture. 11 In the latter 11 years of the study, the mean time to rupture from the index procedure and last follow-up was 4.9 years (range 1.7-13.2 years) and 118 days (range 2.9-297 days), respectively.…”
Section: Late Rupture: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Late complications, such as endoleak, anastomotic aneurysm, graft migration, graft occlusion and new aortic aneurysm formation, have been reported following open or endovascular AAA repair [2,25,26]. Current guidelines recommend repeat aortic imaging and follow-up after AAA surgery, particularly endovascular repair [7,12].…”
Section: Plos Onementioning
confidence: 99%